Validation of analytical method for testing the levels of illicit drugs in Municipal Wastewater influent samples - Mohammad Azimuddin, Izani; Nurul `Azyyati, Sabri; Nurul Nadiah, Hamidon; Kooi Yeong, Khaw; Iekhsan, Othman; Mueller, Jochen; Joo Hui, Tay (Universiti Teknologi MARA, 2022)
Official figures for drug abuse and seizure rates in Malaysia are currently obtained from drug sweep operations carried out by The Royal Malaysia Police (PDRM) in collaboration with The National Antidrug Agency (AADK). This method can provide a useful general picture of drug abuse in our society, but consumption rates and drug use prevalence may be underestimated because the data is obtained directly from consumers. Wastewater-based epidemiology (WBE) has been widely used to objectively monitor population-level drug use, particularly in the Western countries [1-4]. By collecting raw sewage samples from municipal wastewater treatment plants (WWTPs) and quantifying the concentrations of drug residues or its metabolites in the samples, the population-normalized total consumption for a given drug within the population of a sewage treatment service area could be estimated. In this study, an analytical method based on solid phase extraction (SPE) and liquid chromatography tandem mass spectrometry (LC-MS/MS) was validated for the determination of amphetamine (AM), methamphetamine (MA), 3,4-methylenedioxymethamphetamine (MDMA), 3,4-methylenedioxyamphetamine (MDA), and morphine (MOR) in wastewater. The method was tested on sewage samples collected from WWTPs in the Kuantan area to see if it was sensitive enough to detect these compounds. In the future, this method will be applied to assess the consumption of these drugs using the WBE approach.